STUDY ON SOME ASPECTS OF PATHOGENESIS OF RHODOCOCCUS EQUI IN MICE - AL-Khatib, G. M.; Alwan, M. j.; Abdalla, M. S. (The Iraqi Journal of Veterinary Medicine, 2021)
In order to study some aspects of pathogenesis of Rhodococcus equi, 60 white Swiss mice were used. They were randomly divided into 2 groups. The 1s' group (40 animals) was inoculated subcutaneously with a dose of 4x10° CFU .of R.equi while the 2nd group was kept as a control. Four animals from the 1st group and 2 animals from the 2nd group were sacrified at day, 1,2,4,8,12,16,20,24,28 and 30 postinoculation (P.I) Six animals of 1stgroup were died during the first and second days P.I. Microscopical examination showed acute to subacute suppurative inflammation in the liver, lung and spleen at I to 4 days PI. While pyogranulomatous lesions and epithelioid granuloma were seen in liver, lungs and spleen at 4 to 24 days PI R.equi was isolated liver, lungs, spleen, kidney and brain in the first day PI. The bacteria persisted in the spleen from and brain up to 20th day, in the liver up to 24" day while in the lungs, and kidney bacterial isolation continuous till 28th day PI.